Potential of agro-industrial residues from the Amazon region to produce activated carbon - João Rodrigo Coimbra Nobre; Leandro Santos Queiroz; Jonnys Paz Castro; Matheus Felipe Freire Pego; Lisiane Nunes Hugen; Carlos Emmerson Ferreira da Costa; Juliana de Jesus Rocha Pardauil; Luís Adriano Santos do Nascimento; Geraldo Narciso da Rocha Filho; José Roberto Zamian; Elias Costa de Souza; Maria Lucia Bianchi (Heliyon, 2023)
Thousands of tons of residual lignocellulosic biomass are produced and discarded by agroindustries in the Amazon. These biomasses could be harnessed and used in the preparation of activated carbon, in view of the growing demand for this product with high added value, however, little is known about their characteristics, in addition to their potential as precursors of activated carbon. Therefore, the aim of this work was to evaluate the potential of four different biomasses in the preparation and quality of activated carbon. Residues from the processing of the fruits of acai, babassu, Brazil nut, and oil palm were collected, characterized, carbonized, physically activated with CO2, and characterized. The contents of the total extractives, insoluble lignin, minerals, holocellulose, and elemental (CHNS–O) were analyzed. The surface area and surface morphology were determined from the AC produced, and adsorption tests for methylene blue and phenol were performed. The four biomasses showed potential for use in the preparation of CA; the residues presented high contents of lignin (21.83–55.76%) and carbon (46.49–53.79%). AC were predominantly microporous, although small mesopores could be observed. The AC had a surface area of 569.65–1101.26 m2 g−1, a high methylene blue (93–390 mg g−1), and phenol (159–595 mg g−1) adsorption capacities. Babassu-AC stood out compared to the AC of the other analyzed biomasses, reaching the best results.